2008
DOI: 10.3171/ped/2008/1/4/270
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of brainstem tumors: axonal degeneration of motor and sensory tracts

Abstract: Object Diffusion tensor (DT) imaging has been used to predict postoperative motor function in patients with supratentorial tumors. The authors sought to determine whether DT imaging and white matter tractography could detect axonal degeneration in patients with brainstem tumors. Methods A cross-sectional, retrospective study of 7 patients with brainstem tumors and 8 healthy volunteers was performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
0
20
0
3
Order By: Relevance
“…Without applying sophisticated algorithms for correction of susceptibility artifacts, our experience indicated that the quality of DTI datasets in children is sufficient for visualizing and delineating major motor and sensory neural tracts in the brainstem (23-24). However, continued improvements in DTI acquisition, distortion correction, and fiber tractography are needed to further resolve brainstem nuclei, fiber tracts of small caliber, and decussating fibers in the medulla and cerebellar peduncles.…”
Section: Discussionmentioning
confidence: 99%
“…Without applying sophisticated algorithms for correction of susceptibility artifacts, our experience indicated that the quality of DTI datasets in children is sufficient for visualizing and delineating major motor and sensory neural tracts in the brainstem (23-24). However, continued improvements in DTI acquisition, distortion correction, and fiber tractography are needed to further resolve brainstem nuclei, fiber tracts of small caliber, and decussating fibers in the medulla and cerebellar peduncles.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse intrinsic pontine glioma (DIPG) is an extensively invasive malignancy of the brainstem with little notable mass effect (Helton et al, 2008; Caretti et al, 2014). These tumors account for >80% of pediatric brainstem gliomas (Guillamo et al, 2001; Salmaggi et al, 2008; Rineer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Furthermore, fractional anisotropy has been shown to be a good clinical biomarker in detecting the lesions in the brain stem or the posterior fossa, as well as effects of radiation therapy. [19][20][21] Acute stroke lesions in the brain stem are also often missed by DWI because of susceptibility artifacts. 22,23 Here we show that RS-EPI results-qualitatively and quantitatively-in significantly less distortion than SS-EPI in the diffusion trace images, especially at the base of the temporal lobe and the cerebellum.…”
Section: Discussionmentioning
confidence: 99%